Efficient calculation of self - Leung, K.W (IEEE Transactions on antennas and propagation)
This paper presents an analysis of a monopole in free space. The result is given in a concise form that facilitates numerical programming. Moreover, the calculation involves no numerical integration and, thus, the computation is extremely fast